Case report: A case of giant breast skin warts caused by HPV infection - Wang, Chaohui; Zhao, Yuyang; Sun, Zhenhua; Li, Mingjun (Frontiers in Oncology, 2024)
GCA, also known as Buschke-Lowenstein tumor, is a rare sexually transmitted disease associated with HPV types 6 and 111. These warts are considered histologically benign, but there is a risk of localized invasion and development of malignancy. This malignant transformation occurs most often in the perianal and vulvar areas, and involvement of other sites is relatively rare2. In this case, we report a rare case of a giant wart originating from breast skin infected with HPV and progressing to cutaneous squamous cell carcinoma